Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1523/jneurosci.0689-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Visual Stimulus Content in V4 Is Conveyed by Gamma-Rhythmic Information Packages

Abstract: Selective visual attention allows the brain to focus on behaviorally relevant information while ignoring irrelevant signals. As a possible mechanism, routing-by-synchronization was proposed: neural populations receiving attended signals align their gamma-rhythmic activity to that of the sending populations, such that incoming spikes arrive at excitability peaks of receiving populations, enhancing signal transfer. Conversely, non-attended signals arrive unaligned to the receiver's oscillation, reducing signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Gamma phase also modulates orientation selectivity and correlated variability between neurons [68]. This enhancement is modulated by attention [69]. Our results indicate that these effects reflect shifts in somatic sensitivity to excitatory synaptic inputs.…”
Section: Discussionmentioning
confidence: 73%
“…Gamma phase also modulates orientation selectivity and correlated variability between neurons [68]. This enhancement is modulated by attention [69]. Our results indicate that these effects reflect shifts in somatic sensitivity to excitatory synaptic inputs.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, numerous studies have observed systematic changes in the spatiotemporal structure of neuronal activity, such as selective synchronization and desynchronization of oscillatory activity, during cognitive processes such as perception or selective attention that imply meaningful changes in information processing 4,27,28,30,31,42,43 . Therefore, γphase-dependent modulation of neuronal interactions appears to be a widely employed basic mechanism supporting flexible signal and information routing, and network configuration 5,44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…To heighten task difficulty, the stimulus luminance changed randomly with each frame of the screen. For this, a random, integer gray pixel value was selected before each frame update [0 255] corresponding to luminance changes from 0.02 – 45.4 Cd/m 2 , on average 3.8 Cd/m 2 (for details: Grothe et al, 2018; Lisitsyn et al, 2020). From trial initiation until lever release, monkeys had to hold their gaze within a window of 1° diameter centered on the fixation square.…”
Section: Methodsmentioning
confidence: 99%